Model PEIK (Prediksi, Eksperimen, Inferensi, Komunikasi) untuk Pembelajaran IPA di SMP - Rasty Sri Fadiah; Indrawati Indrawati; Sudarti Sudarti (Program Studi Magister Pendidikan IPA FKIP Universitas Jember Bekerjasama dengan Perkumpulan Pendidik IPA Indonesia (PPII), 2017)
This article is the result of development research entitled of PEIK learning model for science learning in junior high school. The objective of this research is produce a learning model that valid, practice, and effective for science lesson in junior high school. The steps of this research using Borg and Gall design. The subject of this research is the students of class VIIA SMP Darul Hikmah Jember. Data collection techniques are tests and observations. Data analysis technique is descriptive qualitative and quantitative. The development research was conducted through 2 cycle, ie limited test (9 students) and class test (1 class). The results showed the average score of validity of the model (3 experts and 3 users) was 87.21 (valid category). Implementation model in the limited test obtained score 11 (good category) and class test obtained score 11 (good category). The effectiveness of the model in the limited test obtained the average score of student activity and student learning outcomes from cycle 1 to cycle 3 are (69.95%; 77.78%; 80.95%) and (0.30; 0.32; 0.58). The average score of student activity and student learning outcomes from cycle 1 to cycle 2 are (80.95%; 87.68%) and (0.70; 0.76). The conclusions of this research are PEIK model (Prediction, Experiment, Inference, Communication) valid, practical and effective for science learning. Keywords: learning model, validity, practicality, and effectivity